The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/foods9050594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yogurt Fermented by Lactobacillus Fermentum TSI and L. Fermentum S2 Derived from a Mongolian Traditional Dairy Product on Rats with High-Fat-Diet-Induced Obesity

Abstract: This study aimed to investigate the metabolic effect of yogurt fermented by Lactobacillus fermentum TSI and S2 isolated from a Mongolian traditional dairy product on rats with high-fat-diet-induced obesity. Quality characteristics of yogurt fermented by commercial starter (CON), L. fermentum TSI2 (TSI2 group), L. fermentum S2 (S2 group), and mixed TSI2 and S2 strains at 1:1 (MIX group), were verified. Six-week-old male Sprague-Dawley rats were divided into five groups and administered the following die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
(32 reference statements)
1
12
0
Order By: Relevance
“…Adiponectin is an adipocyte-derived serum protein that plays an important role in increasing insulin sensitivity [ 153 ]. Adiponectin regulates many metabolic processes including the maintenance of energy balance, glucose homeostasis, and lipid metabolism, and adiponectin levels are generally lower in obese individuals [ 127 ]. It was found that obese rats fed yogurt fermented with Limosilactobacillus fermentum TSI with the high-fat diet had significantly higher adiponectin levels than those fed the high-fat diet alone [ 127 ].…”
Section: Involvement Of Dairy Labs In the Modulation Of Non-communicable Diseases (Ncds)mentioning
confidence: 99%
“…Adiponectin is an adipocyte-derived serum protein that plays an important role in increasing insulin sensitivity [ 153 ]. Adiponectin regulates many metabolic processes including the maintenance of energy balance, glucose homeostasis, and lipid metabolism, and adiponectin levels are generally lower in obese individuals [ 127 ]. It was found that obese rats fed yogurt fermented with Limosilactobacillus fermentum TSI with the high-fat diet had significantly higher adiponectin levels than those fed the high-fat diet alone [ 127 ].…”
Section: Involvement Of Dairy Labs In the Modulation Of Non-communicable Diseases (Ncds)mentioning
confidence: 99%
“…Therefore, nowadays, microbial therapy that includes microbial agents and fecal microbiota transplantation (FMT), which could modulate intertwined microbiota, has emerged gradually as the new candidate to MetS treatment due to the recently published observations in both animal and human studies of its beneficial effects. In animal experiments, it has been demonstrated that oligofructosein, Lactobacillus fermentum TS1 and S2, pasteurized A. muciniphila, and a combination of Lactobacillus and Bacillus subtilis have shown tremendous potential, especially in lipid metabolism in treating MetS (13)(14)(15)(16). In addition, microbial metabolites, such as short-chain fatty acids (SCFAs) contributing to improved glucose homeostasis and insulin sensitivity, were also identified as a therapeutic target for MetS (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Animal experiments and human investigations also showed that Lactobacillus plantarum OLL2712-, Lactobacillus fermentum TSI-, and L. fermentum S2-fermented yogurt prevented insulin resistance and improved lipid metabolism. , …”
Section: Introductionmentioning
confidence: 89%